Bimbingan Teknis Manajemen Masjid sebagai Upaya Mengoptimalkan Fungsi Masjid - Imron Gozali; Sobirin Bagus; Muhammad Imam Syafi'i (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
The focus of this service is to carry out technical guidance on mosque management as an effort to optimize mosque functions for mosques under the guidance of the East Kutai Mosque and Musholla Coordinating Board. The aim is to provide suggestions and input for improvements to mosque administrators in managing and prospering the mosque. The method used is participatory action research where the author is actively involved in direct service activities. The result is that with the existence of the mosque management technical guidance activities, the understanding of mosque administrators about mosque management is better, they get input to carry out mosque functions, and there are more forms of service in mosques, both physical and non-physical services.